Introduction to medical imaging management - Rubenzer, Bernie (CRC Press, 2013)
In the past, for the most part, people who moved into management positions in medical imaging were chosen because they were the best technologists. However, the skill set for technologists and supervisors/managers are vastly different. Even an MBA-educated person may not be ready to take on imaging management. As an example, when buying a very expensive piece of imaging equipment, this person would not necessarily know the right questions to ask, such as: What is my guaranteed uptime? Is technologist training included? Introduction to Medical Imaging Management is a comprehensive reference for.